Løbende nationale reproduktionsregistre og ad hoc data - Jørn Olsen (Norsk Forening for Epidemiologi, 2017)
ENGLISH SUMMARY Olsen J. National registration in human reproduction and research oriented ad hoc data. Nor J Epidemiol 2017; 27 (1-2): 27-31. The Nordic countries have a long tradition for collecting and storing of data in reproductive health. These registers cover the entire population and focus on health outcomes. They have gradually been made available for research and if supplemented with data on potential risk factors in reproductive health, they provide a strong basis for research in potential causes of disease in the reproductive system. Several pregnany/birth cohorts have been successful in providing important information in preventive medicine. The most important of these are the Norwegian birth cohort (MoBa) and the Danish National Birth Cohort (DNBC). Both include about 100,000 newborns. They are based on the rationale that many diseases have causes that start operating in fetal life - fetal programming of diseases - even diseases that manifest themselves later in life (adult diseases). Examples of historic and more recent findings are presented in the following text. Risk of disclosure of personal data is of concern. We have not had examples of such unwanted disclosure and we want to keep this achievement. We clearly have to do many things different and better in the future. Fortunately, technical solutions are available and promising. The registers and the ad hoc data sources have given the Nordic epidemiologists a leading position in reproductive health. To keep that position, we need to plan new cohorts and train more people. If we do that we will be able to continue our collaboration with colleagues all over the world.